Beneficial use of dewatered and composted sewage sludge as soil amendments: behaviour of metals in soils and their uptake by plants - Alvarenga, Paula (2017)
In Portugal, where soils have a very low topsoil organic matter content, the use of sewage sludge (SS) as organic soil improvers seems an attractive option, because it would enable organic matter, N, P, K and other nutrients to be recycled. However, the risk of this practice must be properly assessed. The aim of this study was to evaluate the potential risk of the use of dewatered and composted SS as soil amendments. For this purpose, SS from two different wastewater treatment plants (SS1 and SS2), and a compost produced from SS and agricultural wastes (AWSSC), were characterized for their total metal concentrations, organic contaminants and indicator pathogens, and used in a pot experiment with three application rates, 6, 12 and 24 ton dry matter/ha, cultivated with a hybrid variety of sorghum and Sudan grass (Sorghum bicolor x Sorghum sudanense var. Rocket). SS1 and AWSSC met the legal requirements to be applied to soils, but SS2 had a high content of pathogens, which compromised its use. Both dewatered SS had a marked beneficial effect on plant production and on soil nutritional characteristics, more pronounced than in the case of AWSSC application, without a significant increase in total and in mobile metals concentration in soils. Bioaccumulation factors for metals in plants were low, and their concentrations in the aboveground plant material were lower than the maximum tolerable level for cattle, used as a risk indicator of metal entry into the human food chain. However, it will be necessary, in future studies, to evaluate the potential risk of the observed increase in the mobilisable content of Cu and Zn in soil, as a consequence of the application of these organic materials.